The Influence of Big Five Personality Traits on Social Overload in Active Social Media Users - Rahmah, Ihdina Sazalia; Fakhri, Nurfitriany; Sulastri, Tri (Polteknik Ilmu Pemasyarakatan, 2025)
This research is motivated by social overload which occurs as one of the negative impacts of using social media. The aim of this research is to determine the influence of the big five personalities on the level of social oveload in active social media users. The population in this study are active social media users. The sample in this study consisted of 307 respondents who were active social media users. The sampling technique is nonprobability sampling with the Accidental Sampling method. The data collection method in this research uses a Likert scale with two instruments, namely the social overflow scale and the International Personality Item Pool-Big Five Factor Marker 25 Scale (IPIP-BFM-25). The data analysis technique used is the Spearman correlation test. The results of the analysis test in this study show that there is an influence of the Big Five Personality on Social overload with extraversion, agreeableness and emotional stability which have a significance of <0.05 for active social media users. This study proves that individual personality traits can affect the risk of experiencing social overload. The results found that individuals with high Extraversion traits, agreeableness, and low emotional stability (neuroticism) were more susceptible to social overload. This study also found that individuals who use social media for about one to two hours are still considered safe, compared to individuals who play social media for more than three hours. Therefore, the recommended time for using social media is no more than 3 hours a day.